Characterization of accounting practices of costs and budgets in the productive units of the commune 8 of Villavicencio (GEON Journal (Management, Organizations and Business), 2020)
This article show the result of the investigation project about the identification of accounting practices of cost and the budgets of the productive units in the Villavicencio Commune 8, Ciudad Porfía neighborhood. The study was executed trough of techniques as observation, interviews and surveys that allowed identify and assess the cost management in seventy-three (73) entreprises and evince the main characteristics of the cost management process, planning process, expense budget, control and take decisions. The absence of cost systems, conformation of expenses budget, accounting information analysis in order to take decision result in the close of the establishments. these variables result the factors more comon in these kind of business as well as the informality of their commercial activities and the workers hiring.
Keywords: Accounting; budgeting; Cost; record keeping; Villavicencio